Maneki Neko dalam Sejarah dan Budaya Tionghoa Evolusi dan Pengaruhnya dalam Masyarakat - Ahmad Fajri; Imran Abdoel Gani; Radiatul Adawiyah (Jambura History and Culture Journal, 2026)
Maneki Neko is a cultural symbol originating from Japanese tradition that has been adopted and integrated into Chinese culture and diaspora communities. This study aims to explain the historical origins of Maneki Neko, its reception in Chinese culture, and its influence on economic and spiritual practices. The research method used is descriptive qualitative with a literature review approach, examining various historical, cultural, and contemporary sources. The results show that this symbol originated in Japan during the Edo period and spread to Chinese culture through. trade and migration. Maneki Neko functions as a symbol of attracting fortune and customers in the economy, as well as a spiritual symbol bringing optimism and protection. Maneki Neko demonstrates the close relationship between economics, spirituality, and cultural identity in modern society, becoming a cross-cultural symbol that unites these elements.